2020
DOI: 10.3390/app10113769
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of Soluble Solids Content in Green Plum by Using a Sparse Autoencoder

Abstract: The soluble solids content (SSC) affects the flavor of green plums and is an important parameter during processing. In recent years, the hyperspectral technology has been widely used in the nondestructive testing of fruit ingredients. However, the prediction accuracy of most models can hardly be improved further. The rapid development of deep learning technology has established the foundation for the improvement of building models. A new hyperspectral imaging system aimed at measuring the green plum SSC is dev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 36 publications
0
14
0
Order By: Relevance
“…Traditional autoencoders [32][33][34] are generally fully connected, which will generate a large number of redundant parameters. The extracted features are global, local features are ignored, and local features are more important for wood texture recognition.…”
Section: Methods Of the Local Feature Descriptor Based On The Convolumentioning
confidence: 99%
“…Traditional autoencoders [32][33][34] are generally fully connected, which will generate a large number of redundant parameters. The extracted features are global, local features are ignored, and local features are more important for wood texture recognition.…”
Section: Methods Of the Local Feature Descriptor Based On The Convolumentioning
confidence: 99%
“…By using visible/short-wave near-infrared spectroscopy to establish a partial least squares (PLS) model that can evaluate tomato pH, the results showed that the PLS model offers good prediction ability, with a predicted correlation coefficient of 0.796. Shen [ 13 ] proposed a model combining sparse autoencoder (SAE) and partial least square regression (PLSR) (SAE-PLSR) to predict the soluble solid content of green plum. The correlation coefficient and the root mean square error of the prediction set were 0.9254 and 0.6827, respectively, which indicates excellent prediction performance.…”
Section: Introductionmentioning
confidence: 99%
“…Shen et al combined the PLSR method based on stack self-coding with hyperspectral imaging technology to realize the rapid non-destructive testing of the solid soluble content in green plums [16]. Although this more in-depth learning network has better nonlinearity, due to the increase of the network's depth, the gradient of the backpropagation loss function may disappear during training, so that the weight of the network cannot be effectively adjusted.…”
Section: Introductionmentioning
confidence: 99%